Development of a software tool for rapid, reproducible, and stakeholder-friendly dynamic coupling of system dynamics and physically-based models. (October 2017) - Malard, J.J.; Inam, A.; Hassanzadeh, E.; Adamowski, J.; Tuy, H.A.; Melgar-Quiñonez, H.
Abstract: System Dynamics (SD) modeling is well adapted to developing participatory environmental models. However, SD models are ill-suited for complex physical (e.g., groundwater) processes, and existing methods to couple them with physically-based models tend to be complex and inflexible. We here present Tinamit, a novel tool to couple SD and physically-based models in a rapid, reproducible, and stakeholder-friendly manner. Tinamit requires only a few lines of Python code to couple and simulate models (or, with its interface, no coding at all), which is expected to make model coupling more accessible to stakeholders and allow them to continue developing coupled models after the end of a funded project. We use Tinamit to couple a SD-based farmer economics model from Pakistan with a soil salinity model (SAHYSMOD) and analyze the trade-offs of various policies, of which canal lining with subsidies seemed promising. Such results cannot be readily obtained from either model alone. Highlights: A stakeholder-friendly software tool, Tinamit, was developed. Tinamit facilitates system dynamics (SD) and physically-based model coupling. Tinamit dramatically simplifies the model coupling process. This makes coupled models much more reproducible and accessible to stakeholders. An example of Tinamit's use with soil salinity model in Pakistan is given.